Penerapan Sistem Pembelajaran Bahasa Mandarin Di Beberapa Sekolah Di Indonesia - Sri Haryanti (Lingua Cultura, 2011)
Since Mandarin Language is started to be implemented at schools, many schools begin the learning process of this language. Unfortunately, they do not consider the teacher’s ability in delivering the knowledge. There are a lot of teachers without the basic knowledge of Mandarin but they do the learning activity of this language so that it is undeniable that they found a lot of difficulties in class. Those teachers are not able to transfer the knowledge totally as well as they actually can do. This situation describes negative side to the students related to their studies. In implementing Mandarin class, schools must have specific purpose, nevertheless, it will be much better if the schools consider as well the benefit for the students after they have the class. In accordance to the writer’s experiences since 2006 until now, she tries to describe several facts happening at schools which provide the Mandarin class. The writer use process standard as the reference in writing this paper. She hopes the experiences she writes will be able to give valuable contribution in order to the improvement of teaching and learning process of Mandarin language in the future.